TRANSLATION STRATEGIES APPLIED TO CULTURAL WORDS IN CHARLES DICKENS’ A TALE OF TWO CITIES - Haris Syukri; Rahmadian Harianti; Yuhendra Yuhendra; Nofrika Sari; Afdaleni Afdaleni (STBA Prayoga Padang, 2022)
Abstract This research sees the translation strategies applied to cultural words in Charles Dickens’s A Tale of Two Cities novel translated by Reinitha Lasmana. This research applied the descriptive qualitative method; collecting the data used the observational method by applying a nonparticipant observational technique and analyzing the data using the translational method that employs dividing key factors. In analyzing the data, this research applied both theories of Newmark types of cultural words and translation procedures. However, for the translation strategy, the researcher used Venuti's theories. The findings of this research show three types of cultural words are found in both novels. Secondly, seven procedures are applied in translating selected cultural words. Lastly, it is also found that the most frequent strategy applied by the translator is domestication.